Kajian linguistik kebudayaan terhadap strategi komunikasi IVS dan VSI di Instagram - Shofi, Salsabila As (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
This study aims to examine how the Instagram account @ivs.vsi constructs the cultural meaning of veganism through language practices and how user participation strengthens the collective identity of the vegan community in Indonesia. The study uses a netnography method and is analyzed using Palmer's Cultural Linguistics theory and Henry Jenkins' Participatory Culture theory. Data were collected from five Reels posts on the @ivs.vsi account and relevant user comments. The results show that language is used as a tool of resistance against stigma and as a means to create alternative narratives about local food, nutritional adequacy, and plant-based health. The user community also plays an active role in spreading cultural values through comments, testimonials, and linguistic symbols that reflect the solidarity of Indonesian vegan identity. This research also shows that social media, particularly Instagram, functions not only as a space for sharing information but also as an arena for shaping cultural values and legitimizing alternative.